PRODUKTIFITAS AKADEMISI TEKNOLOGI LABORATORIUM MEDIK DALAM MENGHASILKAN KARYA ILMIAH TRI DHARMA PERGURUAN TINGGI - ASRI JUMADEWI; SAFWAN SAFWAN; ZURIANI RIZKI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The Tri Dharma of Higher Education requires lecturers to carry out educational and teaching activities, research and community service as required in the Lecturer Workload (BKD). This obligation is a demand of almost all universities in Indonesia. Growing motivation and encouragement to lecturers in increasing output in the field of Tri Dharma is considered important to facilitate and develop a culture of writing and publishing academic scientific works. This output will be achieved by providing training and assistance in producing scientific papers. This research was conducted at the Medical Laboratory Technology Study Program (TLM) of the Health Polytechnic of the Ministry of Health of Aceh. This type of research is descriptive with a cross-sectional design, which aims to describe the productivity of medical laboratory technology academics in producing Tri Dharma College scientific papers. The sample of this research is all TLM lecturers, totaling 13 people with total sampling technique. The data collection method was carried out during the pre-test and post-test. The results showed that the post-test increased the results of lecturers' scientific work in the field of education in the form of practical guide books with ISBN as much as 61.5% and textbooks with ISBN as much as 38.5%. Furthermore, the production of scientific works in the field of research increased after being given training in the form of work publication output as much as 46.1%, monograph books with ISBN as much as 30.8%, and obtaining HKI increased to 23.1%. Meanwhile, producing scientific works in the field of community service increased from before being given training to 38.5% of publications in community service journals and 7.7% of books with ISBN. ABSTRAKTri Dharma Perguruan Tinggi mewajibkan dosen untuk melakukan kegiatan pendidikan dan pengajaran, penelitian serta pengabdian kepada masyarakat sebagaimana yang diharuskan dalam Beban Kerja Dosen (BKD). Kewajiban ini menjadi suatu tuntutan hampir semua perguruan tinggi di Indonesia. Menumbuhkan motivasi dan dorongan kepada dosen dalam meningkatkan output di bidang Tri Dharma dirasa penting untuk memudahkan dan mengembangkan budaya menulis dan publikai karya ilmiah akademisi. Output ini akan dapat dicapai dengan memberikan pelatihan dan pendampingan menghasilkan karya ilmiah. Penelitian ini dilakukan di Program Studi Teknologi Laboratorium Medik (TLM) Poltekkes Kemenkes Aceh. Jenis penelitian adalah deskriptif dengan desain crossectional, yang bertujuan untuk mengetahui gambaran produktifitas akademisi teknologi laboratorium medik dalam menghasilkan karya ilmiah Tri Dharma Perguruan Tinggi. Sampel penelitian ini adalah seluruh dosen TLM yang berjumlah 13 orang dengan teknik total sampling. Metode pengambilan data dilakukan saat pre-test dan post-test. Hasil penelitian menunjukkan bahwa post-test meningkatkan hasil karya ilmiah dosen di bidang pendidikan berupa buku penuntun praktikum ber-ISBN sebanyak 61,5% dan buku ajar ber-ISBN sebanyak 38,5%. Selanjutnya, menghasilkan karya ilmiah di bidang penelitian meningkat sesudah diberikan pelatihan berupa output publikasi karya sebanyak 46,1%, buku monograf ber-ISBN sebanyak 30,8%, dan mendapat HKI meningkat menjadi 23,1%. Sedangkan menghasilkan karya ilmiah di bidang pengabdian masyarakat meningkat dari sebelum diberikan pelatihan menjadi 38,5% publikasi karya ke jurnal pengabdian masyarakat dan 7,7% buku ber-ISBN.